Association between respiratory clinical signs and respiratory localization in dogs and cats with abnormal breathing patterns. (November 2021) - Domínguez-Ruiz, M.; Reinero, C.R.; Vientos-Plotts, A.; Grobman, M.E.; Silverstein, D.; Gomes, E.; Le Boedec, K.
Highlights: In dogs and cats, respiratory signs can help localize disease. Inspiratory effort is associated with extra-thoracic airway disease. Expiratory effort is associated with intra-thoracic airway disease. Paradoxical breathing or sound attenuation suggest pleural or diaphragmatic disease. Bronchial disease was linked to crackles and tracheal sensitivity. Abstract: The diagnostic values of respiratory signs have been under-investigated in pets. The study aim was to explore commonly assumed associations between respiratory signs and disease localization in pets with abnormal breathing patterns (ABP). Dogs and cats with ABP presenting to three hospitals were included if investigations permitted disease localization. Hypothesized associations between respiratory signs and disease location were evaluated via mixed-effects logistic regression. Sensitivity, specificity, and positive diagnostic likelihood ratio were calculated. One-hundred and fifteen dogs and 49 cats with ABP were recruited. Confirmed associations included: inspiratory effort with extra-thoracic airway disease (odds ratio [OR], 9.1; 95% confidence interval [95% CI] 3.0–27.2); expiratory effort with intra-thoracic airway disease (OR, 6.5; 95% CI, 2.3–18.1); paradoxical breathing and attenuation of heart/lung sounds with pleural space disease (paradoxical breathing: OR, 4.5; 95% CI 1.7–12.1; sound attenuation: OR, 11.5; 95% CI 4.0–33.3); decreased nasal airflow and stertor with nasal/pharyngeal disease (nasal airflow: OR, 26.2; 95% CI 8.1–84.8; stertor: OR, 155.2; 95% CI 24.9–968.8); stridor with laryngeal or tracheal disease (laryngeal disease: OR, 39.9; 95% CI 7.6–209.0; tracheal disease: OR, 32.4; 95% CI 4.2–248.0); tracheal sensitivity with bronchial disease (OR, 3.8; 95% CI 1.5–9.6); crackles with pulmonary or bronchial disease (pulmonary disease: OR, 5.4; 95% CI 2.1–13.8; bronchial disease: OR, 3.9; 95% CI 1.6–9.8); and goose honking with tracheal disease (all dogs with goose honking had tracheal involvement). Select respiratory signs provide guidance to localize and prioritize causes of the underlying respiratory disease in pets, allowing targeted interventions in animals with ABP.